Kesiapan Provinsi Bandar Lampung Menajadi Bandar Udara Embarkasi Haji - Lita Yarlina (Research and Development Agency of The Ministry of Transportation, 2010)
Lampung Provincial Government to improve its service to the community in furtherance of the pilgrimage, by making Raden Inten II Airport as an airport Lampung embarkation and debarcation pilgrimage between. This study calculates a quantity which is obtained by comparing the revenue cost of the benefit cost ratio (BCR) in the construction/development Roden Inten II Airport to as the embarkation debarkation pilgrimage with Linear Regression formula to calculate forecasting the movement of aircraft and passengers.